Capacity utilization in Indian industry - Chandrasekhar, S (Delhi, 1990)
Indian Industry has registered phenomenal growth in several spheres during the recent decades, but the scope for much greater performance was restricted by certain considerations such as input shortages, lack of suitable industrial planning, presence of global competition through the multinationals, supply constraints and demand distortions, and to a large extent, due to the pervasive phenomenon of capacity underutilization. But for this key factor, the performance profile and the growth rate of Industry could have been even more substantial and greater. This phenomenon itself is attributed to such factors as undesirable inadequate planning, expansions in the production capacities, foreign exchange constraints, energy shortages, and lack of modernization matched by appropriate technology transfers, apart from regions causes and specific to industrial industries, including infrastructure bottlenecks. This study critically deals with an overview of industrial policies and performance of medium and major industry in the Indian economy in general through the planning decades, and analyses the nature of capacity utilization of specific region in recent years, so as to suggest measures for improvement.
Keywords: Industry